Capacity Optimization of Multi-types of Distributed Generators Considering Reliability. Issue 28 (2018) - Zhu, Chengshu; Shi, Linjun; Wu, Feng; Lee, Kwang Y.; He, Weiguo; Lin, Keman
Abstract: In this paper, a method for capacity optimization of multi-types of distributed generators (DG) is presented. Considering the correlation and complementarity of different types of DG, the optimization model is formulated for DGs access to the distribution network. In view of the characteristics of the model, a two-stage Genetic Algorithm (GA), which is improved by changing the mode of generation and the selection process of the population based on the improved GA, is proposed to solve this problem. This method is tested upon IEEE 33-bus system and a real power system. And the influence of reliability of the system is compared when different DGs access to the distribution network, which shows the effectiveness of the optimization method.